TARGET GROUPS OF CONSUMERS OF FASHIONABLE CLOTHING: THE UKRAINIAN CONTEXT - Касс, Б. В.; Пашкевич, К. Л. (Art and Design, 2024)
Purpose: to analyze the types and classification of consumers of the fashion industry for use in the development of clothing collections and the formation of their assortment. Methodology. The research includes an analysis of publications related to the chosen topic and a questionnaire survey among consumers of fashionable clothing to determine the typology of consumers and their preferences, followed by statistical data processing. Results. The work includes an analysis of target groups of fashion clothing consumers. The classification of consumers according to various criteria such as geographic, demographic, psychographic and behavioral factors is determined, which helps manufacturers to choose appropriate methods to attract and encourage purchases of different consumer groups. The distribution of clothing consumers into types, each of which has its own characteristics, behavioral patterns and the level of acceptance of new trends, is analyzed. It has been found that consumer loyalty is considered through cognitive, affective and volitional loyalty, which helps to understand which brands and products consumers choose. A questionnaire survey was conducted, according to which it was determined that there are several types of consumers represented in the fashion industry, which influence the formation of the assortment of clothing collections. The target audiences of modern Ukrainian brands were analyzed and the distribution of various age groups, social status and interests of consumers was determined. Scientific novelty of the obtained results lies in the systematization and classification of fashion clothing consumers based on their behavior and attitude to new trends. Practical significance. The results of the research can be used by clothing designers and marketers of the fashion industry, as they provide information about different categories of consumers, which allows them to more effectively develop and advertise their products, focusing on specific market segments. Also, the research results can be used in the teaching of disciplines related to fashion theory.